STRATEGI PEMASARAN MINYAK SAWIT BERKELANJUTAN (SUSTAINABLE) PADA PT BIO INTI AGRINDO - Angga Yudha Prastya; Luki Karunia; Zahera Mega Utama (Juremi: Jurnal Riset Ekonomi, 2025)
Palm oil (CPO) is a commodity of significant strategic value, evidenced by its robust demand and consumption both domestically and internationally. However, unsustainable land conversion practices have led to environmental repercussions, hindering the acceptance of CPO products in sustainable markets. This research aims to: 1) Identify and analyze internal and external factors that represent strengths, weaknesses, opportunities, and threats; 2) Formulate effective marketing strategies; and 3) Establish priority marketing strategies for sustainable palm oil promotion at PT Bio Inti Agrindo. A SWOT analysis is employed to identify the most effective marketing approach. The findings indicate that, based on the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, the Internal-External (IE) matrix reveals an IFE score of 3.20 and an EFE score of 2.75, placing the company in cell II (Grow and Build). This positioning suggests that the company is internally strong and reasonably adept at managing external challenges. The recommended strategy emphasizes growth and development through expansion. Furthermore, the Quantitative Strategic Planning Matrix (QSPM) analysis yields a Total Attractiveness Score (TAS) of 9 for Strategy 1, 8.6 for Strategy 2, and 8.2 for Strategy 3, leading to the conclusion that the most appropriate strategy is to enhance investment in technology and sustainable innovation.